2007
DOI: 10.1111/j.1442-9071.2006.01385.x
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography analysis of bilateral end‐stage choroidal neovascularization where one eye is treated with photodynamic therapy

Abstract: Based on OCT3 findings, eyes with AMD treated with PDT have a thinner fibrous scar and better preserved retinal thickness when compared with untreated fellow eyes with end-stage fibrotic scarring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…They found that in untreated eyes with end-stage disciform scars, the subretinal scar tended to be thinner than in eyes treated with PDT, in which the scar tended to be thicker but retina tended to be atrophic because of the loss of photoreceptors and neural elements. They also found that the visual acuity in the PDT-treated eyes with more preserved retina was significantly better [11] .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…They found that in untreated eyes with end-stage disciform scars, the subretinal scar tended to be thinner than in eyes treated with PDT, in which the scar tended to be thicker but retina tended to be atrophic because of the loss of photoreceptors and neural elements. They also found that the visual acuity in the PDT-treated eyes with more preserved retina was significantly better [11] .…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, the nature of the scar may have a different effect on central retinal function. Sahni et al [11] compared retinal thickness, subretinal hyper-reflectivity and visual acuity between PDT-treated and fellow eyes that were stable or end-staged AMD. They found that in untreated eyes with end-stage disciform scars, the subretinal scar tended to be thinner than in eyes treated with PDT, in which the scar tended to be thicker but retina tended to be atrophic because of the loss of photoreceptors and neural elements.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, as a volumetric technique, OCT is capable of performing quantitative imaging in situ through segmentation and analysis. In a promising study by Sohni et al, quantitative OCT was used to compare improvements in visual acuity following multiple rounds of PDT with corresponding changes in retinal structure by computing measures of foveal thickness. , As PDT continues to be used to treat AMD, these studies underscore the potential of OCT for monitoring, optimizing, and furthering our understanding of the treatment response.…”
Section: Imaging For Planning Assessment and Monitoring Of Photodynam...mentioning
confidence: 99%